International Commercial Courts - the New Movement in Dispute Resolution - Quan, Dang Van (VNU Journal of Science: Legal Studies, 2023)
Recently, the establishment of international commercial courts in some countries has been creating fruitful changes in the dispute resolution industry. The article provides an overview of dispute resolution mechanisms in international commerce, pointing out that arbitration is the most commonly used mechanism while national courts are the least preferred method. However, both methods have characteristics that need to be improved. On that basis, the author introduces the birth of the international commercial court, approaching the research object from definition, and history and analyzing some salient characteristics by examining some typical international commercial courts that have been founded in Singapore, the United Arab Emirates (Dubai) and the UK (London). For some vital features of the international commercial court, the author analyzes them in  comparison with those of arbitration and national courts so that readers may assure of the strengths and weaknesses of these three methods. Finally, after considering the number of caseloads heard in international commercial courts and confirming the potential development of this court model, the author comes to a proposal for Vietnam regarding researching, surveying, and building an international commercial court.